Community-Based Prevalence Estimates of Chlamydia trachomatis and Neisseria gonorrhoeae Infections Among Gay, Bisexual, and Other Men Who Have Sex With Men in Montréal, Canada. Issue 12 (24th December 2021) - Harvey-Lavoie, Simonne; Apelian, Herak; Labbé, Annie-Claude; Cox, Joseph; Messier-Peet, Marc; Moodie, Erica E. M.; Fourmigue, Alain; Moore, David; Lachowsky, Nathan J.; Grace, Daniel; Hart, Trevor A.; Jollimore, Jody; et al.
Abstract : This first community-based study among gay, bisexual and other men who have sex with men in Montréal, Canada shows that if testing was limited to the urogenital site, 80% and 94% of Chlamydia trachomatis and Neisseria gonorrhoeae infections, respectively, would have been missed. Supplemental digital content is available in the text. Abstract : Background: Reported cases of Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) infections are increasing among Canadian men. Estimates of community-based CT/NG prevalence are lacking among gay, bisexual, and other men who have sex with men (GBM). Methods: Respondent driven sampling was used to recruit GBM in Montréal, Canada between February 2017 and June 2018. Specimens provided from urogenital, rectal, and pharyngeal sites were analyzed using nucleic acid amplification test to detect CT/NG. Prevalence estimates of CT/NG, overall and by anatomical site were calculated. All estimates are respondent-driven sampling–adjusted. Results: Among 1177 GBM, the prevalence of rectal, urogenital, pharyngeal and overall were respectively 2.4%, 0.4%, 0.4%, and 2.8% for CT infections, and 3.1%, 0.4%, 3.5%, and 5.6% for NG infections. If testing had been limited to the urogenital site, 80% and 94% of CT and NG infections, respectively, would have been missed. Conclusions: This community-based study among GBM shows that the CT prevalence was about half of that observed for NG. A large part of CT/NG infections involves only the extragenital sites, highlighting the need for systematic multisite screening regardless of symptoms. In the mist of the COVID-19 pandemic and the limited CT/NG screening capacity due to test kits shortage, it might be considered to prioritize rectal and pharyngeal CT/NG testing over urogenital testing in asymptomatic GBM.